Viewing Technology Integration in Current Classroom Through Triple-E Framework - Pratama, Putu Yoga Sathya (Proceedings Series on Physical & Formal Sciences, 2022)
Employing Triple-E Framework, this research aimed at describing the effectiveness of technology tools used in the classroom to foster learning objectives. The research was conducted qualitatively through descriptive design. 14 junior high school teachers from a private school in Denpasar, Bali, Indonesia, were participated to further be observed. The observations were conducted through the assistance of Triple-E Framework as the main instrument, along with note taking and close reading technique to obtain references from sources. The obtained data were analyzed inductively through the utilization of interactive data analysis, consisted of data collection, data reduction, and conclusion drawing. The results portray attractive findings around classification of technology tools’ effectiveness and dispersion of teachers’ digital literacy competence. The analysis showed there were more observed teachers classified into exceptional connection teachers rather than those who perform some and even low connection teachers. In addition, it seemed that the integration of technology tools in current classroom can assist both teachers and students in achieving the learning objectives, although it is underlined by several terms and conditions. Further rigorous researches are suggested to conduct, prior to the finding of this research as one of main references.